2004
DOI: 10.1089/aid.2004.20.1063
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and Antiapoptotic Effects of CXCR4: Is It a Matter of Intrinsic Efficacy? Implications for HIV Neuropathogenesis

Abstract: CXCR4, the specific receptor for the chemokine SDF-1α that also binds CXCR4-using HIV gp120s, affects survival of different cell types, including neurons. However, current data show that the outcome of CXCR4 activation on neuronal survival may vary depending on the ligand and/or the cellular conditions. In this study, we have systematically compared the effects of SDF-1α and gp120 IIIB (with or without CD4) on several intracellular pathways involved in cell survival, including MAP kinases and Akt-dependent pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 60 publications
9
55
0
Order By: Relevance
“…In line with these studies, acute stimulation of neurons (in the absence of glia) with DAMGO, a selective μ-opioid peptide, or with CXCL12, the natural CXCR4 ligand, induced phosphorylation of both ERK1/2 and Akt ( Figures 1F and 2). As previously reported, time-course and dose-response experiments indicated that peak responses occurred around 5 min after treatment with DAMGO (1 to 10 μM; Figure 2) and 15 min with CXCL12 (20 nM; Khan et al, 2004, Meucci et al, 1998.…”
Section: Cortical Neurons Coexpress Mor and Cxcr4supporting
confidence: 83%
See 3 more Smart Citations
“…In line with these studies, acute stimulation of neurons (in the absence of glia) with DAMGO, a selective μ-opioid peptide, or with CXCL12, the natural CXCR4 ligand, induced phosphorylation of both ERK1/2 and Akt ( Figures 1F and 2). As previously reported, time-course and dose-response experiments indicated that peak responses occurred around 5 min after treatment with DAMGO (1 to 10 μM; Figure 2) and 15 min with CXCL12 (20 nM; Khan et al, 2004, Meucci et al, 1998.…”
Section: Cortical Neurons Coexpress Mor and Cxcr4supporting
confidence: 83%
“…One such effect is the activation of the antiapoptotic kinase Akt that is required for the neuroprotective action of chemokines (Meucci et al, 2000;Khan et al, 2004). The ability of μ-opioid peptides to compromise stimulation of mitogen-activated protein (MAP) kinases by CXCL12, though, suggests that proteins regulating crucial steps of CXCR4 signaling, such as those involved in receptor desensitization and recycling, might be affected by opioids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest that the neurotoxicity caused by both viral proteins may be regulated by MAPKs. Gp120-induced increases in JNK phosphorylation, as well as intracellular Ca 2+ levels and ERK phosphorylation, in rat hippocampal neurons (Khan et al, 2004); however, the role of JNK in survival was not assessed. In another study, alterations in JNK through manipulation of its upstream kinase mixed-lineage kinase-3 (MLK3) prevented gp120-CXCR4 triggered death in cultured rat hippocampal neurons (Bodner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%